2021
DOI: 10.15446/recolma.v54n2.93833
|View full text |Cite
|
Sign up to set email alerts
|

Certain Properties of Square Matrices over Fields with Applications to Rings

Abstract: We prove that any square nilpotent matrix over a field is a difference of two idempotent matrices as well as that any square matrix over an algebraically closed field is a sum of a nilpotent square-zero matrix and a diagonalizable matrix. We further apply these two assertions to a variation of π-regular rings. These results somewhat improve on establishments due to Breaz from Linear Algebra & amp; Appl. (2018) and Abyzov from Siberian Math. J. (2019) as well as they also refine two recent achievements due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results can be viewed and treated as the development of method and ideas presented in [8] and [6], respectively. Some closely related studies can also be found in [5].…”
Section: Introduction and Conventionsmentioning
confidence: 94%
“…The results can be viewed and treated as the development of method and ideas presented in [8] and [6], respectively. Some closely related studies can also be found in [5].…”
Section: Introduction and Conventionsmentioning
confidence: 94%